Zambia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the improved near-term outlook for the Zambian economy in recent months, driven by good rains and the rising world copper price. The economy was in near-crisis conditions from the fourth quarter of 2015 through most of 2016, reflecting the impact of exogenous shocks and lax fiscal policy in the lead-up to general elections. The medium-term outlook for the economy is contingent on policies. Achieving sustained high and inclusive growth requires a stable macroeconomic environment as well as policies and reforms to increase productivity, enhance competitiveness, strengthen human capital and support financial inclusion for small and medium-scale enterprises.